BioSoundSCape: A bioacoustic dataset for the Fynbos Biome - Andrew A. Turner; Matthew L. Clark; Leo Salas; Colleen Seymour; Rose L. Snyder; Alan T. K. Lee; Antonio Ferraz; Fabian Schneider; John Measey; Johan Huisamen; Daniël Cloete; Sally D. Hofmeyr; et al. (Scientific Data)
Abstract Most biodiversity data are collected at fine spatial scales, but threats to species and ecosystems occur at broad spatial scales. Remote sensing allows broad-scale assessment of biodiversity but these data need to be ground-truthed with contemporaneous in situ datasets. Various faunal groups produce sounds or vocalizations which can then be related to remotely-sensed data. As part of the NASA-led BioSCape project, the BioSoundSCape project deployed Autonomous Recording Units (ARUs), which record sounds in an approximately 50 m radius, at 521 sites spread across an area of approximately 119,058 km2 in the Greater Cape Floristic Region, South Africa, during the wet and dry seasons of 2023. The ARUs recorded sounds one in every ten minutes, over 4–10 days, producing 825,832 minutes of recordings (approximately 400,000 minutes of recording in each season). These sound data are georeferenced to within 20 m, with time and date information, so may be useful for relating biodiversity patterns in soundscapes to vegetation structure, fire history, plant phenology, distance to roads and other human infrastructure.